2018
DOI: 10.1038/s41598-018-22488-2
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of miRNA Isoforms and tRNA Fragments in Prostate Cancer

Abstract: MicroRNA (miRNA) isoforms (“isomiRs”) and tRNA-derived fragments (“tRFs”) are powerful regulatory non-coding RNAs (ncRNAs). In human tissues, both types of molecules are abundant, with expression patterns that depend on a person’s race, sex and population origin. Here, we present our analyses of the Prostate Cancer (PRAD) datasets of The Cancer Genome Atlas (TCGA) from the standpoint of isomiRs and tRFs. This study represents the first simultaneous examination of isomiRs and tRFs in a large cohort of PRAD pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 57 publications
(73 reference statements)
10
55
0
Order By: Relevance
“…Previously, we showed that tRFs have links to precision medicine and hold promise for furthering our understanding of homeostasis and disease. Specifically, we demonstrated that the identity and abundance of tRFs depend on a person's sex, population origin, and race/ethnicity, as well as tissue, tissue state, and disease type (5,8,19). We also found that the associations ("wiring") of tRFs with mRNAs and molecular pathways is race/ethnicity-specific in prostate adenocarcinoma (8) and triple-negative breast cancer (19).…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Previously, we showed that tRFs have links to precision medicine and hold promise for furthering our understanding of homeostasis and disease. Specifically, we demonstrated that the identity and abundance of tRFs depend on a person's sex, population origin, and race/ethnicity, as well as tissue, tissue state, and disease type (5,8,19). We also found that the associations ("wiring") of tRFs with mRNAs and molecular pathways is race/ethnicity-specific in prostate adenocarcinoma (8) and triple-negative breast cancer (19).…”
Section: Introductionmentioning
confidence: 78%
“…The production of tRFs changes in response to factors like diet variations (6) and trauma (7). It has also been shown that tRFs are produced in a tissue-dependent manner (5), exhibit differential abundances in cancer compared to normal tissue (8,9), and are involved in transgenerational inheritance (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has already been shown that, in humans, these endpoint variations are constitutive in both healthy individuals and patients [10,24,25]. In fact, isomiRs have been shown to depend on a person's sex, population origin, and ethnicity [10,24], as well as on tissue, tissue state, and disease subtype [26,27]. Nontemplated nucleotide additions at the 3'-end can be due to nucleotide transferases (TUTase) that generally add adenine or uridine nucleotides [28].…”
Section: Resultsmentioning
confidence: 99%
“…miRDeep2 scores a miRNA by considering the hairpin folding, the mature, star and loop sequence from the hairpin, and the proportion of nucleotides in the mature miRNA passing the RNA folding threshold from the randfold software (Bonnet et al 2004; Lorenz et al 2011) (Github: ebOO/randfold). If multiple sequences reached the same highest miRDeep2 score, the consensus sequence was the sequence with the highest frequency across all libraries. If multiple sequences reached the same highest frequency, the consensus sequence was the longest sequence. If multiple sequences reached the same longest length, the consensus sequence was the collapsed sequence from the stack (this only applies to mature and star sequences). The consensus miRNA genomic coordinates and miRNA sequences were considered as “clean” miRNAs and were retained for analysis. Note, the observation that a stack of reads aligning to the same known precursor, mature or star miRNA varied in length in this lactating dairy cow, is similar to the miRNA isoforms that were detected in healthy humans, where depending on gender, population and race, precursor miRNAs gave rise to many isoforms that typically differed in either 5’ or 3’ termini or both, and the most abundant isoform was frequently annotated as the canonical sequence in miRBase (Telonis et al 2015; Magee et al 2018). However, miRNA isoform was out of the scope of this study, and our method to obtain consensus sequence didn’t consider miRNA isoforms.…”
Section: Methodsmentioning
confidence: 71%